2023
DOI: 10.1186/s40001-022-00967-7
|View full text |Cite
|
Sign up to set email alerts
|

Insights into research on myocardial ischemia/reperfusion injury from 2012 to 2021: a bibliometric analysis

Abstract: Background Numerous studies on myocardial ischemia/reperfusion (MI/R) injury have been undertaken in recent years. Hotspots and developmental trends in MI/R research are being rapidly updated. However, there has been no bibliometric analysis that systematically evaluates existing literature on MI/R injury. Our study explores developments in MI/R research over the past decade, and provides a reference for future research. Materials and methods Both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…40 In the present study, we investigated the role of circHIPK3, a functional circRNA, in diverse diseases. 21,41 Placental tissues and plasma specimens, frequently utilized as experimental materials, [42][43][44] were collected from pregnant women to estimate circHIPK3 levels in these samples. The expression of circHIPK3 increased evidently in GDM placental tissues and plasma samples compared to that in GDM-free samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 In the present study, we investigated the role of circHIPK3, a functional circRNA, in diverse diseases. 21,41 Placental tissues and plasma specimens, frequently utilized as experimental materials, [42][43][44] were collected from pregnant women to estimate circHIPK3 levels in these samples. The expression of circHIPK3 increased evidently in GDM placental tissues and plasma samples compared to that in GDM-free samples.…”
Section: Discussionmentioning
confidence: 99%
“…Circ‐PNPT1 facilitates GDM by modulating the miR‐889‐3p/PAK1 axis in trophoblast cells 40 . In the present study, we investigated the role of circHIPK3, a functional circRNA, in diverse diseases 21,41 . Placental tissues and plasma specimens, frequently utilized as experimental materials, 42–44 were collected from pregnant women to estimate circHIPK3 levels in these samples.…”
Section: Discussionmentioning
confidence: 99%
“…In myocardial ischemia, Bai et al. demonstrated that circHIPK3 inhibits proliferative capacity and induces heart cells to apoptosis by binding with miR-124-3p ( 31 ). Chaofang Lian et al.…”
Section: Circular Rna Hipk3mentioning
confidence: 99%
“…Previous studies have demonstrated that MI/R injury results from a complex interplay of pathological events upon reperfusion, including oxidative stress, inflammatory responses, and mitochondrial dysfunction [ 4 ]. Despite these insights, developing effective therapeutic agents to target MI/R injury remains challenging [ 2 5 ]. This underscores the need for a deeper understanding of its molecular mechanisms and the identification of novel therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%